The Impact of Managerial Skills, Organizational Communication, Discipline, and School Climate on Work Engagement in Schools - Asmara, Yeni; Sulistiyo, Urip; Rosmiati, Rosmiati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study explores the impact of managerial skills, organizational communication, discipline, and school climate on work engagement among teachers and staff in educational institutions. While work engagement is essential for improving school performance and student outcomes, factors influencing it in schools remain insufficiently understood. The research aims to identify specific elements within these four areas that foster higher work engagement, providing insights to enhance teacher satisfaction and productivity. Using a quantitative approach, data will be collected through surveys distributed to teachers and staff across various schools. A structured questionnaire will measure levels of managerial skills, organizational communication, discipline, school climate, and work engagement. Statistical methods, including multiple regression analysis, will analyze the relationships between these variables. The study’s findings are expected to offer practical recommendations for school leaders and policymakers to cultivate a supportive, productive working environment. By presenting an integrated approach, this research contributes to the field by examining the combined effects of multiple factors on work engagement, offering a comprehensive model for enhancing teacher engagement in schools.